Using Life Satisfaction and Happiness Data for Environmental Valuation: An Experienced Preference Approach - Susana Ferreira; Mirko Moro; Heinz Welsch (Institute of Labor Economics (IZA), 2024)
A growing literature in economics uses subjective well-being data collected in surveys as a proxy for utility. Environmental economists have combined these data with the public goods experienced by respondents using a novel non-market valuation approach: the experienced preference approach. In this review, we take stock of what we know, including recent developments, and what we still need to learn about this new approach. We first present a conceptual framework that clarifies the relationship between experienced preference and conventional valuation approaches. We then discuss key challenges for its empirical application and identify areas where additional research would be fruitful.
Keywords: Q51; I31; H41; 330; subjective well-being; life-satisfaction; happiness; experienced utility; non-market valuation; willingness to pay; public goods